2018
DOI: 10.1002/mawe.201700122
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of work‐hardening behavior of dual phase steel by heat treatment

Abstract: The work‐hardening response and mechanical properties of dual phase steels originated from different initial microstructures under low and high martensite volume fractions were investigated using a typical carbon‐manganese steel. The modified Crussard‐Jaoul analysis was used for studying the work‐hardening stages and the deformation behavior of ferrite and martensite. It was revealed that the initial martensitic microstructure before intercritical annealing is much better than the full annealed banded ferritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…As a result of rolling of the as-received sample, the pearlite colonies and the ferrite grains became pancaked along the rolling direction (Figure 5(b)). Subsequent isothermal heating at 775 °C results in the recrystallisation of ferrite grains and also the formation of much finer equiaxed ferrite grains and spheroidised carbides [4446] in the former pearlite colonies (FPC) as can be seen in Figure 5(c,d).
Figure 5 Microstructural evolution of IH725 sample after intercritical annealing at 775 °C.
…”
Section: Resultsmentioning
confidence: 99%
“…As a result of rolling of the as-received sample, the pearlite colonies and the ferrite grains became pancaked along the rolling direction (Figure 5(b)). Subsequent isothermal heating at 775 °C results in the recrystallisation of ferrite grains and also the formation of much finer equiaxed ferrite grains and spheroidised carbides [4446] in the former pearlite colonies (FPC) as can be seen in Figure 5(c,d).
Figure 5 Microstructural evolution of IH725 sample after intercritical annealing at 775 °C.
…”
Section: Resultsmentioning
confidence: 99%
“…There have been many similar investigations, which confirmed that intercritical annealing of the initial martensitic microstructure resulted in DP steel with better combination of strength and ductility in comparison with any other non-deformed initial microstructures due to the well distributed martensite islands within a ferritic matrix [36,39,47-51]. The reason originates from the nature of martensite, which exhibit high density of lattice defects in form of pockets, blocks, laths that are suitable sites for phase nucleation during intercritical annealing.…”
Section: Prior To Intercritical Annealingmentioning
confidence: 99%
“…The martensite phase is known as one of the main constituent phases in the advanced high-strength steels, which has been extensively studied by Bleck and coworkers [18][19][20] and Mirzadeh and coworkers [21][22][23]. However, owing to their high strength and brittleness, the martensitic steels are normally used in the quenched and tempered condition.…”
Section: Introductionmentioning
confidence: 99%